Transition-metal-free and base promoted C–C bond formation via C–N bond cleavage of organoammonium salts. Issue 38 (7th September 2021) - Zhang, Tao; Wang, Kunyu; Ke, Yuting; Tang, Yuanyuan; Liu, Long; Huang, Tianzeng; Li, Chunya; Tang, Zhi; Chen, Tieqiao
Abstract : Only mediated by KO t Bu, a deaminative carbon–carbon bond forming reaction of organoammonium salts with benzyl C(sp 3 )–H bond was developed. Abstract : A transition-metal-free and base promoted C–C bond forming reaction of benzyl C(sp 3 )–H bond with organoammonium salts via C–N bond cleavage has been reported. Benzyl ammonium salts as well as cinnamyl ammonium salt could couple readily with various benzyl C(sp 3 )–H species, producing the corresponding products in moderate to excellent yields with good functional group tolerance. Late stage chemical manipulation enabled the specific 1, 2-diarylethane structure of products transformed into useful olefin compounds via dehydrogenation, which further demonstrated the utility of this reaction.